Factors Shaping the Future of the Global Economy and Finance - To Ngoc Hung; Nguyen Dinh Trung (Review of Business and Economics Studies)
The global financial system emerged in the aftermath of World War II, playing a crucial role in the global economic and geopolitical landscape dominated by developed nations. However, the world is currently undergoing rapid changes. Developing countries are assuming increasingly important roles and positions in the global economy. The robust resurgence of Russia’s military and political power as a superpower, along with China’s rise in economic, technological, and military domains, is unveiling a new global order. Furthermore, the relentless development of digital technology is profoundly and comprehensively reshaping the economic, social, and political fabric of nations worldwide. Global issues such as climate change and population aging play significant roles in shaping the future of the global economy and finance. The research objective is to reveal and analyze the main factors shaping the future of the global economy and finance. The article employs a qualitative research method with analysis, synthesis and commenting on secondary sources of information from related studies. The authors conclude that six main relevant factors can influence the future of the global economy and finance: (i) the development of digital technology; (ii) geopolitical situation; (iii) the international role of the US dollar; (iv) climate change; (v) population aging; (vi) the inevitability of structural transformation.